2001
DOI: 10.1001/jama.286.24.3115
|View full text |Cite
|
Sign up to set email alerts
|

Quinolones and False-Positive Urine Screening for Opiates by Immunoassay Technology

Abstract: Greater attention to the cross-reactivity of quinolones with immunoassays for opiates is needed to minimize the potential for invalid test interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 32 publications
0
42
0
3
Order By: Relevance
“…The medico-legal consequences of testing in the workplace encourage great attention towards control of false positive results. Commonly prescribed drugs such as fluoroquinolone antibiotics have been reported to produce false positive results in some opiate immunoassays [19]. While confirmatory testing can correct for these false positive immunoassay results, this comes at significant cost since the confirmatory testing is a highly labor-intensive process unlike automated immunoassay testing.…”
Section: Urine Screening For Opioidsmentioning
confidence: 99%
“…The medico-legal consequences of testing in the workplace encourage great attention towards control of false positive results. Commonly prescribed drugs such as fluoroquinolone antibiotics have been reported to produce false positive results in some opiate immunoassays [19]. While confirmatory testing can correct for these false positive immunoassay results, this comes at significant cost since the confirmatory testing is a highly labor-intensive process unlike automated immunoassay testing.…”
Section: Urine Screening For Opioidsmentioning
confidence: 99%
“…When enzyme immunoassay techniques are used for urine screening, a falsepositive result for opiates in a patient taking levofloxacin may lead to erroneous clinical decisions and inadvertent litigation. [1][2][3][4] Baden and colleagues found that even a single dose of levofloxacin can interact with the enzyme immunoassay screening test, and the false-positive result for opiates can remain positive for 24 hours or more depending on the clearance of levofloxacin from the system. In their study involving six healthy volunteers, the researchers tested the crossreactivity of 13 different quinolones with five commercial opiate screening assays.…”
Section: Discussionmentioning
confidence: 99%
“…Levofloxacin, ofloxacin and pefloxacin most consistently caused false-positive results. 1 Fluoroquinolones are not the only medications that may cross-react with enzyme immunoassay urine screening tests. Others include commonly used over-the-counter medications such as ibuprofen and dextromethorphan (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Rifampicin, a drug usually used in the treatment of tuberculosis, interferes with opiate immunoassays (Daher 2002). Other drugs that contribute to false-positive urine screens for opiates are the quinolone group of antibiotics (Baden 2001) and cardiac drugs such as verapamil (Lichtenwalner 1998).…”
Section: Opioidsmentioning
confidence: 99%